Neuroprotective effects of Morinda officinalis How.: Anti-inflammatory and antioxidant roles in Alzheimer’s disease - Zhang, Yi; Zhang, Meng (Frontiers in Aging Neuroscience, 2022)
ABSTRACT Pharmacological studies have shown that some traditional Chinese medicines (TCMs) have applications in the treatment of Alzheimer’s disease (AD). Morinda officinalis How. (MO) is a TCM with a long history and is widely used to tonify kidney Yang. In vitro and in vivo experiments have suggested that MO contains various effective pharmaceutical components and chemicals, including oligosaccharides, anthraquinones, iridoids, flavonoids, amino acids, and trace elements, conferring MO with anti-inflammatory and antioxidant properties. Neuroinflammation and oxidative stress are undoubtedly hallmarks of neurodegeneration, contributing to AD progression. In this mini-review, we summarize the molecular mechanisms, structure-activity relationships, and potential synergistic and antagonistic effects of active components in MO. This discussion highlights the roles of these active components, such as oligosaccharides, anthraquinones, and iridoid glycosides, in the treatment of AD via anti-inflammatory and antioxidant mechanisms, providing a scientific basis for further utilization of MO.